Collaborative Damage : An Experimental Ethnography of Chinese Globalization - Bunkenborg, Mikkel; Pedersen, Morten Axel, 1969-; Nielsen, Morten, 1971- (Book collections on Project MUSE., 2022)
"A comparative anthropological study of Chinese globalization, this book explores the emergence of a global polity and the implications of collaborative endeavors and failures through ethnographic fieldwork on Chinese infrastructure and resource-extraction projects in Mongolia and Mozambique"--